As an Application of Sustainability: Utilizing Processed Rice Husk to Remove Cadmium Ions Cd (II) From Aqueous Phase by Adsorption - Saja Farhan Rewaeh; Hatem A. Gzar; Marwaa K. Azeez (Wasit Journal of Engineering Sciences)
This study goals to reduce the importance of expensive commercial activated carbon while removing heavy metals from wastewater using cheap, locally available materials (rice husk). To accomplish this goal, a variety of pH values were tested, and it was found that batch studies at pH 5 had the best Cadmium ion removal effectiveness. 180 minutes was determined to be the ideal contact time for the process, and it was discovered that as contact time increased, adsorption effectiveness increased. 180 rpm is the recommended shaking speed, given studies on how agitation speed influences batch adsorption. The effectiveness of the rice husks capacity to eradicate Cadmium Cd (II) from aqueous solutions and absorb it, has assessed. The study revealed that Cd had a 98% effectiveness of removal. The recommended adsorbent's maximum Cd adsorption capability in a batch system was found to be 7.38 mg/g. Three models— Freundlich, Temkin, and Langmuir—were fitted to various equilibrium isothermal experiments. For this system, the experimental best fit was provided by the Freundlich isotherm model, with an value of 0.97. The equilibrium isotherms were discovered to be of a favorable type. When the correlation coefficient (R2) values of each curve for the four models are compared, it appears that the Elovich model best captures the kinetics of the Cadmium ions adsorption onto rice husk. Were the values (Elovich> pseudo-second order> intra-particle diffusion> Pseudo-First Order). According to the research, rice husk may be useful for filtering out wastewater from contaminants and impurities. So, It is a good alternative for expensive activated carbon.